KERJASAMA EKONOMI INDONESIA-JAPAN ECONOMIC PARTNERSHIP AGREEMENT (IJEPA) TERHADAP PERDAGANGAN BATUBARA INDONESIA-JEPANG TAHUN 2019-2021 - Aulya Rafly Salsabil; Putri Hergianasari; Suryo Sakti Hadiwijoyo (STIA Bina Banua Banjarmasin, 2022)
This study aims to analyze the effect of IJEPA on coal trade which affects Indonesia's economic development through the import-export sector. IJEPA is an economic cooperation that includes cooperation in the manufacturing industry, agriculture, fisheries, forestry, trade, human resources, tourism and mineral resources with the aim of improving the economy by utilizing the export, import and coal sectors. Using descriptive qualitative methods with literature studies and interviews, the results of the research show that the establishment of IJEPA can strengthen economic relations, open access to the Japanese market and to gain profits between Indonesia and Japan.